Eufemisme Bahasa Gaul di Group WhatsApp Dosen Segawon Reborn dalam Spektrum Pendidikan Islam - Rahman, Rifqi Aulia; El Syam, Robingun Suyud; Nugroho, Muhamad Yusuf Amin (MAN 4 Kota Pekanbaru, 2024)
This article aims to describe colloquial euphemisms in the WhatsApp Group “Segawon Reborn” among lecturers within the context of the Islamic education spectrum. This descriptive-qualitative research employed reading-recording techniques and interviews with the subjects of lecturers at Universitas Sains Al-Qur’an Wonosobo, which were analyzed using the Milles and Huberman model. It showed that slang euphemisms are used in daily conversations with the choice of elegant language to avoid inappropriate expressions. Lecturers still preserve good communication in the spectrum of Islamic education for politeness and comfort, avoiding disaster, disguising meaning, reducing shame, and carrying out religious orders. Using slang euphemisms could reduce the impact of conflict due to misunderstanding. The study recommends that lecturers refrain from using slang euphemisms without losing communication ethics.